Investigating dynamics of complex system irradiated by intense x-ray free electron laser pulses. (March 2015) - Fang, L; Jurek, Z; Osipov, T; Murphy, B F; Santra, R; Berrah, N
Abstract: We carried out experimental and theoretical investigation of the response of a complex molecule, C60, to intense x-ray photon beam from a free-electron-laser. We show good agreement between the modelling and the experiment. Our model, which can be scaled well to larger systems, reveals femotosecond molecular dynamics details, at the level of atomic resolution, which are inaccessible directly by our experiments. Our results illustrate the variety of physical and chemical processes in the interaction between large molecules and intense x- ray pulses, including photoelectric effect, secondary ionization, recombination and inter-atomic Auger decays. The understanding of these processes has a broad impact on research that implements intense x-ray pulses.